“… Infections are not confined in labs…”: Community engagement for Controlled Human Infection Studies: Opinions of researchers, bioethicists and research regulators in Uganda - Winfred Nazziwa; Stella Neema; Alison M. Elliott; Samson B. Kaboko; Erisa Mwaka (PLoS ONE, 2026)
Controlled human infection studies play a critical role in advancing our knowledge of infectious diseases and developing therapeutics. However, these studies involve knowingly exposing research participants to pathogens, raising significant ethical, social, environmental and logistical concerns. Controlled human infection studies are being conducted in settings where individuals are economically disadvantaged and may have limited access to healthcare, education, and basic social amenities, making community engagement a central element in ensuring the ethical conduct of controlled human infection studies and the protection of participants’ rights. In a cross-sectional qualitative study, we explored the views of research stakeholders on how to effectively engage local communities on controlled human infection studies. Twenty-seven key informant interviews were conducted with researchers, bioethics experts, research ethics committee members, and staff at national research regulatory bodies in Uganda between September 2023 – March 2024. A systematic inductive analysis approach was used. Due to the complexity and sensitivity of controlled human infection studies, findings reveal the necessity for early planning, adequate budgets and broad-based engagement using multiple approaches and activities. Research participants viewed the bottom-up approach as more appropriate for engaging communities. They also argued that meaningful community engagement should be a continuous process grounded in respect, justice and partnership, rather than merely a procedural or regulatory obligation. The acceptability and success of controlled human infection studies in low resource settings largely depends on effective intentional community engagement in the entire research process.